2021
DOI: 10.7759/cureus.16363
|View full text |Cite
|
Sign up to set email alerts
|

Curing Benign Paroxysmal Positional Vertigo (BPPV) Through Telehealth: A Case Series

Abstract: Benign paroxysmal positional vertigo (BPPV) is a common medical condition in which the patient feels a spinning sensation when making certain head movements. There is evidence to support those free-floating calcium crystals in the semi-circular canals (the inner ear) may be the cause. BPPV can be a disabling condition. It can be easily diagnosed after taking a careful history and performing bedside examinations. BPPV can be treated successfully through a specific set of physical maneuvers leading to the remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…16,17 Due to the limited access to medical care provider during the COVID-19 pandemic, telemedicine for diagnosis and treatment of BPPV was proposed as a good alternative. [18][19][20] To our knowledge, this study is the first to examine the impact of COVID-19 on the incidence of BPPV subtypes by hospital visit (OPD vs ER), and the mean time interval between vertigo onset and primary evaluation. Our data demonstrated that the total number of BPPV patients who were diagnosed in the ER and OPD decreased by 15.9% (517 to 435) during the…”
mentioning
confidence: 99%
“…16,17 Due to the limited access to medical care provider during the COVID-19 pandemic, telemedicine for diagnosis and treatment of BPPV was proposed as a good alternative. [18][19][20] To our knowledge, this study is the first to examine the impact of COVID-19 on the incidence of BPPV subtypes by hospital visit (OPD vs ER), and the mean time interval between vertigo onset and primary evaluation. Our data demonstrated that the total number of BPPV patients who were diagnosed in the ER and OPD decreased by 15.9% (517 to 435) during the…”
mentioning
confidence: 99%
“…Hence, specific diagnostic positional maneuvers can be used to induce vertigo and nystagmus in order to identify the affected semicircular canal by analyzing the characteristics of the nystagmus. The otolith can be moved to the utricle by correct repositioning (9).…”
mentioning
confidence: 99%